BESARNYA RESIKO KEGEMUKAN TERHADAP KADAR GULA RENDAH - Sihadi Sihadi; Sri Poedji Hastoety Djaiman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2005)
ABSTRACT Background: The beta pancreas cell hypertrophy and hyperinsulinime occur in Obesity. If the compensation is not sufficient and with the addition of genetic and environment factors, diabetes mellitus are more likely to occur. The general parameter utilized to determine the condition of diabetes mellitus is blood glucose level, therefore the analysis of obesity risk to blood glucose level are performed. Objectives: To determine the relation of the risk of obesity level to the blood  glucose level. Methods: The secondary data are analyzed based on SKRT 2004 and Susenas 2004 data. All the samples are female and male with the age among 25-65. Results: The people with obesity are 1.78 times more likely to have high blood glucose level than person with normal weight. The other variable is that the female have less risk of 0.72 times and 0.62 times to have borderline and high blood glucose level compared to male. The age groups of 36-45 and 46-65 have risk 1.28 times and 1.52 times respectively, to have high glucose level than the age group of 25-35. Another result shows that the people living in the city are 1.30 times more likely to have high blood glucose level than those living in countryside. Conclusions: The people with obesity are more risky to have high blood glucose level than people with normal weight. The other risk factors of borderline or high blood glucose level are men, living in city and above 36 years of age. Recommendations: The education about blood glucose level should be given priory to the risk groups which are; the people with obesity, male, living in city and more than 36 years of age. [Penel Gizi Makan 2005,28(1): 9-15] Keywords: overweight, obesity, blood glucose level